2015
DOI: 10.1007/s11606-015-3222-9
|View full text |Cite
|
Sign up to set email alerts
|

How Can eHealth Technology Address Challenges Related to Multimorbidity? Perspectives from Patients with Multiple Chronic Conditions

Abstract: BACKGROUND: Patient eHealth technology offers potential support for disease self-management, but the value of existing applications for patients with multiple chronic conditions (MCCs) is unclear. OBJECTIVES: To understand self-management and health care navigation challenges that patients face due to MCCs and to identify opportunities to support these patients through new and enhanced eHealth technology. DESIGN: After administering a screening survey, we conducted 10 focus groups of 3-8 patients grouped by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
141
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(150 citation statements)
references
References 31 publications
8
141
0
1
Order By: Relevance
“…1 More than 75% of all health care costs are due to chronic diseases. Therefore, effective management of chronic diseases is a major focus of current health policy.…”
mentioning
confidence: 99%
“…1 More than 75% of all health care costs are due to chronic diseases. Therefore, effective management of chronic diseases is a major focus of current health policy.…”
mentioning
confidence: 99%
“…Verbal discussions were possible, but often the phone line was invoked to ask for clarification. Although members reported high levels of satisfaction with this virtual real-time format, 43 the results are limited by the participants and their willingness to share their ideas.…”
Section: Discussionmentioning
confidence: 89%
“…In these situations, patients are often responsible for synthesizing their own potentially disparate or conflicting management plans or care recommendations. 43 Care coordination is one possible solution, and a growing number of studies have shown mixed results depending on the patient population. 44 Sharing best practices for achieving high-value care through online collaborations is another possible solution.…”
Section: Finding Value Opportunities In Large Organizationsmentioning
confidence: 99%
“…Several studies report that eHealth is promising with regard to selfmanagement support, and that people with chronic conditions desire tools that effectively reduce the limitations of life caused by disease [34][35][36].…”
Section: Discussionmentioning
confidence: 99%